Spring 2013 FYS Classes - Kansas State University, K-State First (Kansas State University. K-State First., 2013)
Course Listings for first-year seminar classes for the 2013 spring semester. The academic content of FYS classes is the same as other sections of the same course, but enrollment is limited to first-year students in sections of 22 or fewer. FYS classes emphasize communication, critical thinking, and community building. Students benefit from a learning environment built around engagement, interaction, and application of concepts. All classes count as a K-State 8, general education class.
Keywords: First-year seminars; Course list; K-State 8; Spring 2013; Enrollment; General Education; Fliers (printed matter)